Quality Assessment of Smoked Shrimps (Traditional and Improved)Stored at Room Temperature (28 To 32°C) in Different Packs - Hossain, MI; Shikha, FH; Mursalin, MS (Journal of Environmental Science and Natural Resources, 2021)
To preserve shrimps, smoking or smoke curing is an ancient methods in practice since long before. The present study was conducted to prepare improved smoked shrimp from 4 different species of raw shrimps, namely Chali (Metapenaeus brevicornis), Chaka (Penaeus indicus), Horina (Metapenaeus monoceros) and Khogda (Parapenaeopsis stylifera) at laboratory condition, to observe the changes in sensory, biochemical and microbiological parameters of the both laboratory and traditionally prepared (at Koyra, Khulna) smoked shrimps of these species. The initial moisture level of improved smoked shrimps (Chali, Chaka, Horina and Khogda) ranged from 14.22±0.02%~16.15±0.03% with the highest value in Khogda, but the moisture content of traditional smoked Chali was 17.53±0.11%. After storage of 120 days the moisture reached to the ranged from 15.12±0.13% to 18.83±0.21%, protein content from initial 61.18± 91%~64.05±0.41% to 52.8 ±51%~57.61±0.84%, lipid content from initial 9.73±0.06%~10.05± 0.06% to 8.55±0.04%~9.10±0.06% and ash contents from initial 11.06±0.14%~16.36±0.08% to 14.28±0.08%~19.11±0.07%. For TVB-N values and microbial load also a same increasing trend was observed for the samples. From the obtained results of the study it could be concluded as- implementation of improved techniques for smoking able to extend the storage period of smoked shrimps and among different packs vacuum sealed pack is the most effective one for storage. Environ. Sci. & Natural Resources, 12(1&2): 181-190, 2019